If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x^2-6x=3
We move all terms to the left:
9x^2-6x-(3)=0
a = 9; b = -6; c = -3;
Δ = b2-4ac
Δ = -62-4·9·(-3)
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{144}=12$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-12}{2*9}=\frac{-6}{18} =-1/3 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+12}{2*9}=\frac{18}{18} =1 $
| 5a(8-a)=3a-20 | | 4p/7-7=27 | | y=5.2^× | | 5y-35+3=-12 | | 3+8t=-4+9t | | 2(b+3)-9=b-11 | | z/5-4=2/2/3 | | 3/4x-6=1/4×+8 | | 8z+17=6z+34 | | -4(-5n+6)+5n=-124 | | 2n-5=3(n+2) | | -10=4p+2-3p | | x=6x+49=5x+59 | | x/6=5/18 | | 6x+7=23;3 | | 3/4+(2x+1)=2 | | 13-c=9 | | 3p-1=5p-5-14-2p | | X2-4x=12 | | 3x+8-2(x+4)=12 | | -(x+4)-2x=8-(x-3 | | y/6+2=-9 | | -6(2-2x)=-84 | | 7y-(2y-4)=39 | | -8=2(u+5)-5u | | 200m-100m+52,250=55,825-175m | | 6x+8=8-3x | | 2^(x+1)+4^(x-1)-1152=0 | | 22=9x | | 3x+8-2(x+14)=12 | | 13=-3x-3x+7 | | 125m-75m+48500=51000-200m |